Layanan Polres Bima Kota dalam Penanganan Kasus Kecelakaan Lalu Lintas pada Anak di Bawah Umur Ditinjau dari Manajemen Konflik - Agung Iswahyudi; Florentina Ratih Wulandari; Darmanto Darmanto (Universitas Pamulang, 2023)
The aim of this research is to determine the services for handling traffic accident cases for minors in terms of conflict management and the factors that hinder Bima City Police services in handling traffic accident cases for minors in terms of conflict management. The police as a public service institution need to carry out one of their duties related to traffic. The results of the research show that the Bima City Police service in handling traffic accident cases involving minors has been carried out well through the criminal mediation that can be offered, where the police act as a mediator between the perpetrator and the victim/victim's family members. The inhibiting factors in resolving cases of children who are perpetrators of traffic accident crimes consist of two things, namely internal obstacles in the form of uniting thoughts between the victim and the child (perpetrator) in order to reach an agreement, and human resources (HR) of the police specifically for children in handling cases. child. Next are external obstacles in the form of limited adequate facilities and infrastructure in the diversion process, different understandings in handling children in conflict with the law among law enforcement officials, community understanding regarding diversion and regulations regarding supervision of the implementation of the results of diversion agreements.